2013
DOI: 10.1186/1471-2164-14-415
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptome profiles of Camellia sinensis during cold acclimation

Abstract: BackgroundTea is the most popular non-alcoholic health beverage in the world. The tea plant (Camellia sinensis (L.) O. Kuntze) needs to undergo a cold acclimation process to enhance its freezing tolerance in winter. Changes that occur at the molecular level in response to low temperatures are poorly understood in tea plants. To elucidate the molecular mechanisms of cold acclimation, we employed RNA-Seq and digital gene expression (DGE) technologies to the study of genome-wide expression profiles during cold ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
222
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(237 citation statements)
references
References 74 publications
14
222
1
Order By: Relevance
“…In these varieties, 1711 genes were upregulated while 1402 were downregulated, with 394 common genes (Winfield et al, 2010). In tea plant (Camellia sinensis), 1770 differentially expressed genes were reported; of these, 1168 were upregulated and 602 were downregulated under cold stress (Wang et al, 2013). In this study, we have identified a total of 5205 DEGs.…”
Section: Analysis Of Differentially Expressed Genesmentioning
confidence: 89%
“…In these varieties, 1711 genes were upregulated while 1402 were downregulated, with 394 common genes (Winfield et al, 2010). In tea plant (Camellia sinensis), 1770 differentially expressed genes were reported; of these, 1168 were upregulated and 602 were downregulated under cold stress (Wang et al, 2013). In this study, we have identified a total of 5205 DEGs.…”
Section: Analysis Of Differentially Expressed Genesmentioning
confidence: 89%
“…Standard transcriptome annotation included BLAST alignments against the NCBI nonredundant (NR) database and the COG database as well as GO and KEGG annotations. However, in some works an extensive annotation has been done also by alignments against EST databases (Wang et al 2013b , d ;Lee et al 2013 ), the From Pertea et al ( 2003 ) TAIR10 database (Wang et al 2013d ), or the PlantGDB database ).…”
Section: Coldmentioning
confidence: 99%
“…In the second case, researchers studied the transcriptomes of tropical or other cold-sensitive plants useful in biotechnology or horticulture. Among them has been Jatropha curcas L., an oil-rich tropical shrub with multiple uses, including biodiesel production (Wang et al 2013b ), Anthurium andraeanum , one of the most popular tropical fl owers (Tian et al 2013 ), and the tea plant Camellia sinensis (Wang et al 2013d ).…”
Section: Coldmentioning
confidence: 99%
“…Several techniques, such as DNA microarrays, Expressed Sequence Tags (ESTs), Serial Analysis of Gene Expression (SAGE), Digital Gene Expression (DGE) profi ling, and Next-Generation Sequencing (NGS)-based tools such as RNA sequencing (RNA-seq) are being exploited to capture and identify the differentially regulated genes during stress conditions in plants (Cramer et al 2011 ;Lister et al 2009 ;Wang et al 2013 ) (Table 6.2 ). It provides an in-depth knowledge of the global gene expression pattern of plant response to stress stimuli (Jung et al 2003 ).…”
Section: Transcriptomics Approachmentioning
confidence: 99%